Gambaran Darah Katak Fejervarya limnocharis di Lahan Pertanian yang Menggunakan Pestisida di Sumatera Barat - Yelvita Sari; Djong Hon Tjong; Resti Rahayu (Biogenesis: Jurnal Ilmiah Biologi, 2016)
Fejervarya limnocharis are amphibians which generally can be found in agriculture area. The high intensity of pesticide application in agricultural area can lead to alteration of physiological aspects of organism inhabiting that area. Quantitative examination of hematology aspect can be conducted to evaluate physiological condition of species. This research was aimed to find out about hematology profile of F. limnocharis living in agriculture area using pesticide in West Sumatera. Thus, examinations of erythrocytes, leukocytes, hemoglobin concentrations, and hematocrit values collected from F. limnocharis living in three different areas have been conducted. The data gained have been compared with normal blood value of various amphibians species from previous research. The result acquired respectively for three locations show that total of erythrocytes were in normal range, which were 1,616 x 106/mm3; 1,539 x 106/mm3; and 1,712 x 106/mm3; hemoglobin concentration were lower than normal range, which constituted 4,06 g/dL; 4 g/dL; and 4,18 g/dL; hematocrit values have normal range, which made up 40,06 %; 40,14 %; and 45,7 %; total of leukocytes were higher than normal range, which were 27,450/mm3; 49,934/mm3; and 22,040/mm3. Usage of pesticide in agriculture area causes alteration of some hematological aspect.Keywords: Fejervarya limnocharis, hematology profile, pesticide, West Sumatera